1985
DOI: 10.1111/j.1365-3180.1985.tb00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Competition between annual weeds and vining peas grown at a range of population densities: effects on the weeds

Abstract: Resum^: ZasammenfassungLinear regression of dry weight of weeds against crop density, together with the use of diversity indices and principal component analysis were used to derive inforniLition about changes in the behaviour of annual weeds over the growing season and in response to a wide range of crop densities in vining peas Pi.sum sativunt L. Using linear regression it was possible lo quantify reductions in weed dry weights per unit increase in crop plant density. The "weed loss" factor was acceptably co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
1
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 10 publications
1
16
1
1
Order By: Relevance
“…Nelson and Nylund (1962) Increasing field pea plant density significantly reduced weed biomass in 2 of 3 yr. Several studies have shown that increasing field pea populations reduce weed biomass (Marx und Hagedo* 196l; Lawson and Topham 1985; iownley-Smith-and Wright 1994), but none reported significant di-fferences among cultivars' In this study, while the The cultivar-by-seeding-rate interaction was significant n^J994 and 1995 only, while the cultivar 2n4 segling rate effects were significant in 1993. In all 3 yr, seed /ields increased with field pea plant density.…”
contrasting
confidence: 53%
“…Nelson and Nylund (1962) Increasing field pea plant density significantly reduced weed biomass in 2 of 3 yr. Several studies have shown that increasing field pea populations reduce weed biomass (Marx und Hagedo* 196l; Lawson and Topham 1985; iownley-Smith-and Wright 1994), but none reported significant di-fferences among cultivars' In this study, while the The cultivar-by-seeding-rate interaction was significant n^J994 and 1995 only, while the cultivar 2n4 segling rate effects were significant in 1993. In all 3 yr, seed /ields increased with field pea plant density.…”
contrasting
confidence: 53%
“…The significant difference between the weed biomass in the replacement intercrop and in the additive intercrop confirms the observation that weeds decrease as crop density and biomass increases. Similar results on the relationship between crop density and weed biomass were reported by Lawson & Topham (1985). In a review of the literature on the effects of intercropping and crop rotation on weed productivity, Liebman & Dyck (1993) reported mixed results (unfortunately based on a flawed vote-counting approach; see Gurevitch & Hedges 1993) on the success of intercrops in suppressing weed biomass.…”
Section: Weed Biomassmentioning
confidence: 53%
“…Obviously, in this case, the crop sowing date can be used as a weed management tool only in those environments where the farmer can actually choose whether to sow wheat in autumn or in spring and not, for example, in Mediterranean‐type environments, where wheat can only be sown in autumn. In vining pea ( Pisum sativum L.), an increase in the seeding rate may turn into a higher competitive ability, but often to the detriment of grain yield because of the concurrently higher intraspecific competition (Lawson & Topham, 1985). Similarly, in potato ( Solanum tuberosum L.), a higher planting density may turn into a crop competitive advantage but may also decrease tuber quality and increase crop susceptibility to diseases (Litterick et al ., 1999).…”
Section: Building Up a Good Weed Management Systemmentioning
confidence: 99%